Dystopian Reality of Human Existence in Contemporary Indian Society - Khurana, Dr Payal (SMART MOVES JOURNAL IJELLH, 2017)
“Bhog & Other stories,” (2010) a debut collection of short stories by Ankur Betageri can be considered as an anthology of man’s emptiness in life. The characters envisaged by the author appear true to life dealing with the existential problems faced by the contemporary society. The paper highlights the issues faced by present day homo-sapiens, which is leading to mayhem and chaos in the society. The topsy-turvy life that we all are leading is brought to surface, which signals a society where life would be nightmarish and gloomy. Betageri has offered a collection of fourteen stories which stir the Indian psyche and give a panoramic view of not only the Indian society but the human existence on the whole. Each story corresponds to different issues and enigmas faced by humans; and thus offer variety of themes that every reader can associate with himself.